Efecto de los Ingresos Permanentes sobre el Delito: Un Enfoque Espacial y un Caso de Aplicación (2014)
This paper analyzes the impact of increment in the permanent income on crime in each spatial unit and their neighbors. Different specifications of spatial panel data are estimated to capture the effects of spatial distribution and income on crime. In the particular case of Medellin, the estimated impact of increase 1% in permanent income in specific commune is a decrease in crime near to 0,67%, and the effects of each neighbor are variable and significant. Tests statistics can show the robustness of the conclusions and the adequate specification of the model.